Efektivitas Media Flashcard terhadap Kemampuan Numerasi Anak Usia Dini - Velantika, Giza; Setyowati, Heni; Dinawati, Mega; Khoiriyah , Khoiriyah; Kusumaningtyas, Nila (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Numeracy skills are a crucial aspect of early childhood cognitive development, playing a key role in fostering logical and systematic thinking as well as problem-solving abilities. This study aims to improve children’s numeracy skills through the use of flashcards in Group A at RA IT Cendekia Kebonagung Demak. This study employed the Classroom Action Research (CAR) method, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The study sample comprised 10 children. Data collection techniques involved observation and documentation. The results indicated that the children’s numeracy skills showed significant improvement in each cycle. In the pre-cycle stage, most children were in the “Not Yet Developed” and “Beginning to Develop” categories. After the intervention in Cycle I, there was an improvement to the “Developing as Expected” category, and in Cycle II, most children reached the “Developing Very Well” category at 78%. The use of flashcards proved effective in improving children’s ability to recognize number concepts, recite numbers, use number symbols, group objects, and understand the concepts of “many” and “few” through concrete and enjoyable learning activities. Thus, flashcards can be used as an effective learning strategy in developing numeracy skills in early childhood.